2019
DOI: 10.1039/c8ta12070f
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the electronic structure of CuWO4 thin films for enhanced photoelectrochemical water splitting

Abstract: CuWO4 is an n-type oxide semiconductor with a bandgap of 2.2 eV which exhibits great potential for photoelectrochemical (PEC) conversion of solar energy into chemical fuels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 51 publications
9
85
1
1
Order By: Relevance
“…As mentioned above, the electronic structure of CuWO 4 is still an open question and there have been models suggested by several authors. For instance, Tian et al 8 reported that the bottom of the conduction band of CuWO 4 comes from Cu 3d orbitals while the top of the valence band is formed by Cu 3d orbitals and O 2p orbitals. Hoang et al 14 pointed out that O 2p orbitals are dominant in the valence band of CuWO 4 while its conduction band is formed mainly by Cu 3d orbitals and W 5d orbitals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned above, the electronic structure of CuWO 4 is still an open question and there have been models suggested by several authors. For instance, Tian et al 8 reported that the bottom of the conduction band of CuWO 4 comes from Cu 3d orbitals while the top of the valence band is formed by Cu 3d orbitals and O 2p orbitals. Hoang et al 14 pointed out that O 2p orbitals are dominant in the valence band of CuWO 4 while its conduction band is formed mainly by Cu 3d orbitals and W 5d orbitals.…”
Section: Discussionmentioning
confidence: 99%
“… 7 It is known as an n-type semiconductor and its valence band is believed to be composed mainly of oxygen 2p states that are hybridized with tungsten and copper s, p, and d states. 8 , 9 The conduction band contains mainly W 5d states hybridized with the oxygen 2p states. In addition, it has been claimed that the single Cu 3d hole contributes to the bottom of the conduction band, which shifts the conduction band minimum in CuWO 4 downward compared to WO 3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Nonetheless, the progression of adsorption method is slow and time consuming and necessitates a huge amount of adsorbent for operative environmental remediation. [20][21][22] In recent years, photo-catalytic technology has received more and more attention due to its high efficiency, low cost, and environmental friendliness. 23,24 However, the photocatalytic activity of photo-catalytic technology for high concentrations of pollutants is still insufficient.…”
Section: Introductionmentioning
confidence: 99%